Rapid In-Field Approaches for Delineating VOC in Both Soil Vapour and Groundwater for Vapour Intrusion Assessment - Wang, Liang; Cheng, Ying; Naidu, Ravi; Gell, Peter; Bowman, Mark (Frontiers in Environmental Science, 2021)
Traditional contaminated site characterisation approaches are time-consuming, labour-intensive, and demand a high level of expertise. This case study provides a rapid field-based solution to investigating a VOC contaminated site and its vapour incursion by combining soil vapour and groundwater survey. To fully assess the volatile organic compound (VOC) distribution in a contaminated site, a number of self-developed soil vapour sampling probes (SVSP) were placed vertically at different locations in a grid with different depths. Hence, 3D subsurface contour maps for VOC concentrations in soil vapour can be obtained and used to help identify hot spots and the migration patterns of VOCs. This SVSP is easy to install in the field and a cost-effective solution for the rapid assessment of soil vapour samples. The SVP can be installed either vertically or horizontally. If there is a requirement to take soil vapour samples beneath an existing building from a potential contamination source zone, SVSPs can be horizontally installed beneath the building without compromising its structural integrity. In addition, to ascertain the correct groundwater channels that are likely to carry contaminants from a potential source zone, an electrical resistivity tomography technique was employed to provide the preliminary information for groundwater delineation in a complex groundwater channel network.